2017
DOI: 10.1002/vms3.66
|View full text |Cite
|
Sign up to set email alerts
|

Pilot assessment of vascular endothelial growth factor receptors and trafficking pathways in recurrent and metastatic canine subcutaneous mast cell tumours

Abstract: Canine subcutaneous mast cell tumour (scMCT) shows less aggressive biological behaviour than cutaneous MCT. Vascular endothelial growth factor receptor 2 (VEGFR2) is expressed by neoplastic cells in canine scMCT, but the relevance of this signalling pathway for disease pathobiology is not clear. The objective of this study was to quantify VEGF‐A, VEGFR2, pVEGFR2, the VEGF co‐receptor Neuropilin 1 (NRP‐1) and the E3 ubiquitin protein ligase c‐Cbl in canine scMCT, and to evaluate their association with disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…To determine the expression of the markers in the tendons of the animals, the whole section was evaluated; afterwards, five fields of each fragment with the greatest expression were selected. For CD172a and microvascular density (MVD -anti-factor VIII) evaluation, the percentage of stained cells was determined using the ImageJ program by establishing a "threshold" according to Da Silva et al (2017), which determined the percentage of stained cells. In addition, a grid reticle count of the field-stained lymphocytes was carried out for the CD3 antibody (a total of 5 fields per sample).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…To determine the expression of the markers in the tendons of the animals, the whole section was evaluated; afterwards, five fields of each fragment with the greatest expression were selected. For CD172a and microvascular density (MVD -anti-factor VIII) evaluation, the percentage of stained cells was determined using the ImageJ program by establishing a "threshold" according to Da Silva et al (2017), which determined the percentage of stained cells. In addition, a grid reticle count of the field-stained lymphocytes was carried out for the CD3 antibody (a total of 5 fields per sample).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…VEGFC and vascular endothelial growth factor D are both vascular endothelial growth factors (VEGFs) involved in the maintenance of normal adult endothelial cells, proliferation and the increase in vascular permeability and were found expressed by human vascular neoplastic cells [ 5 , 21 , 22 , 23 , 24 , 25 ]. In a previous study on canine vascular tumors, VEGFR-3 expression was found in the majority of hemagiosarcomas investigated, suggesting that this marker would not be suitable for the immunohistochemical discrimination between malignant and benign vascular tumors [ 26 , 27 , 28 ]. In contrast, the expression of VEGFC has been found limited to neoplastic endothelial cells in hemangiomas with capillary differentiation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…For immunohistochemistry analysis, a qualitative evaluation describing each marker immunolocalization was performed. Immunohistochemical expression was evaluated using ImageJ software (ImageJ v1.47; NIH, Bethesda, MD, USA) according to the methods of Da Silva et al [21]. Briefly, a threshold tool was determined for Claudin-5 and PSMA expression based on positively stained cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Among the markers used in veterinary oncology, Ki-67 is a nuclear protein widely used for the evaluation of cell proliferation. This protein is expressed only in proliferating cells and in all active phases of the cell cycle, including early division, and observed mainly in patients at a late stage with poor prognosis [21]. Besides its importance in veterinary oncology, to the best of our knowledge, no previous study has reported the prognostic value of Ki67 in canine HSA.…”
Section: Introductionmentioning
confidence: 99%